PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DEVIDEN, DAN RASIO AKTIVITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR PADA SEKTOR INFRAKSTRUKUR YANG TERDAFTAR DI BEI PERIODE 2020-2023 - Gadis Puspita Sari; Aminda Tioni Sihombing; Mesrawati Mesrawati; Christina verawaty Situmorang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to analyze the effect of investment decisions, financing decisions, dividend policies, and activity ratios on the value of manufacturing companies in the infrastructure sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. The research method used is a quantitative method with a multiple linear regression approach to test the relationship between independent variables and dependent variables. The results of the study indicate that investment decisions, financing decisions, and dividend policies do not have a significant effect on company value. Meanwhile, the activity ratio has a negative and significant effect on company value. Partially, only the activity ratio affects company value, while other variables do not show a significant effect. This finding indicates that asset management efficiency has a greater impact on company value compared to investment decisions, financing, and dividend policies